The strength of conspiracy beliefs versus scientific information: the case of COVID 19 preventive behaviours - Pinazo-Calatayud, Daniel; Agut-Nieto, Sonia; Arahuete, Lorena; Peris, Rosana; Barros, Alfonso; Vázquez-Rodríguez, Carolina (Frontiers in Psychology, 2024)
The COVID-19 pandemic represents a massive global health crisis with unprecedented global impacts on individuals' health and daily lives (Heymann & Shindo, 2020;Lin et al., 2020). It goes beyond infection produced by a lethal member of a large coronavirus group called SARS-CoV-2 because it significantly affects individuals' psychological (e.g., anxiety, stress, depression, etc.) and social (e.g., isolation, elderly poverty, etc.) health (e.g., Ali Jadoo, 2020; Lin et al., 2020;Saladino et al., 2020). Efforts are being made to accelerate the development, manufacturing, and equitable access of COVID-19 vaccines for all countries (World Health Organization, 2021). Meanwhile, uncertainty, people doubting the precise causes of COVID-19 and exposure to conspiracy rhetoric and fake news about its origins, severity and prevention are spreading.Conspiracy beliefs in the virus being everywhere might lead people to distrust current scientific information (e.g., SARS-CoV-2 is not a laboratory construct or a purposefully manipulated virus, Andersen et al., 2020).Such COVID-19 conspiracy beliefs are associated with less adherence to government guidelines and excessive mistrust (Freeman et al., 2020;Karić & Međedović, 2021), and are likely to have negative, rather than positive, expectations of the post-COVID-19 future. All this may have evident negative implications for people's health and public policies; for instance, being less willing to engage in prosocial and preventive behaviours to mitigate viral spread. This study sought to better understand how such